Ex libris Jan Rhebergen / [Jaroslav Lukavský]. - Lukavský, Jaroslav (1924-1984) ([wydawca nieznany], 1967)
Naga dziewczyna kąpiąca się w morzu, koło niej pływają ryby, u dołu napis: Ex libris Jan Rhebergen.